Transmedia Storytelling no B2B: o caso de estudo do StorySD - Ana Filipa Sousa Alves (2017)
The human brain is highly evolved and provides an extraordinary communication capacity, written, verbal and gestural. This ability makes us social beings, able to live in groups and create complex bonds. The language has evolved quickly, just like the act of telling stories. Nowadays, storytelling has a fundamental role because it allows us to draw the attention of others and to transmit knowledge. When we tell stories, we can make use of different communication channels, thus originating transmedia storytelling, which is telling a story through multiple platforms, where each platform gives a valid and unique contribute to the story. This research intends to understand and evaluate the impact of the use of the transmedia storytelling strategy in B2B communication, specially the interaction of the brand in the digital platforms. The investigation model for this dissertation includes the analysis of case studies and the production of the first series of the project StorySD. This project teaches what is transmedia storytelling and how to apply it as a communication strategy. The data gathering related to the project and the answers of a form that was shared in the end of the first series, allowed us to conclude that this project was overall successful, identifying the advantages and disadvantages of the platforms that were used. This research contributes to obtained the best practices in the application of transmedia storytelling to B2B and to the emergence of the field of investigation of transmedia storytelling. Keywords: transmedia storytelling, marketing, social media